‘They Tell Me I’m Dangerous’: Incarcerated Mothers, Scandinavian Prisons and the Ambidextrous Penal–Welfare State - Ystanes, Vilde (The British journal of criminology, 2020)
Ambidextrous states can grasp citizens with both the welfare/support-oriented left hand and the punishment/control-oriented right hand. When people go to prison in such contexts, they may simultaneously face punishment and welfare interventions. Based on interviews with six women serving prison sentences in Norway for violence against their own children, this article discusses certain aspects of the prison experience in welfare-state prisons. Their criminal sentences, and the associated stigma and feelings of shame, weighed heavily on these women, but they eventually felt the state’s welfare-oriented left hand was tighter and more punitive than the right hand. This article describes their experiences and strategies in coping with the challenges they faced as prisoners in an ambidextrous state.